Keterkaitan Social Media Terhadap Customer Satisfaction - Ristiana, Adelea; Ria Selvira; Sari, Widiana; Kristaung, Robert (Ekonomi Digital, 2022)
This study aims to analyze the effect of social media activity, social media interactivity and social media content on customer satisfaction in fashion products. The methodology of this research is quantitative with a total sample of 105 respondents using purposive sampling. This research was conducted by distributing online questionnaires using a google form. The research hypothesis was tested using the Structural Equation Model (SEM) with the software used by AMOS. The results showed that social media activity, social media interactivity and social media content had a positive effect on customer satisfaction. Based on the three test results that have the greatest influence on customer satisfaction, namely on social media activity. The results of this study will assist in developing consumer satisfaction for fashion products that allow academics and practitioners to formulate operational strategies that are honed to optimize consumer satisfaction and profitability in fashion products. This study discusses the shortcomings and gaps in previous research. These findings provide a better understanding of consumer satisfaction.